Studi Komparasi Tafsir Lathaif Al-Isyarat Dan Tafsir Ibnu Katsir dalam Penafsiran Surat Al-Ma’Un (LPPAIK Universitas Muhammadiyah Bandung, 2023)
This writing aims to find out the comparison of the interpretation of Lathaif Al-Igest by Imam Qusyairi with the interpretation of al-Qur'an al-Azhim by Ibn Kathir based on the sources, methods, styles, and systematics. The research was conducted qualitatively using a comparative approach. The results show that in terms of manhaj, the two works of interpretation use the manhaj tahlili with the systematics of mushafi's tartib. Tafsir Ibnu Katsir uses sources in the form of bil qur'an, bil hadith, bi qoul sahabi, qoul tabi'i, mufassir's opinion, and lughah rules on certain verses, while Imam Qusyairi's interpretation is only with hadith. Tafsir ibn katsir, which in several verses includes asbabunnuzul, has a variety of styles, including fiqh, ra'yi and qira'at, with the systematic tartib mushaf. While the interpretation of Imam Qusyairy has a style of fiqh, philosophy, and Sufism.